Effect of harvesting time and drying methods on aflatoxin contamination in groundnut in Mozambique - Jnr, Emmanuel Zuza; Muitia, Amade; Amane, Manuel I V; Brandenburg, Rick L; Emmot, Andrew; Mondjana, Ana M (Journal of Postharvest Technology, 2018)
The production and utilization of groundnut (Arachis hypogea L) has increased tremendously across all provinces of Mozambique in recent times. However, the presence of mycotoxins, especially aflatoxins has remained a critical food concern in both the human and livestock diet. In this study, the effect of harvesting time and drying methods on aflatoxin contamination were examined at two locations namely; Nampula Research Station (PAN) and Mapupulo Agricultural Research Center in Nampula and Cabo Delgado provinces respectively. A randomized complete block design in a split-split plot arrangement with four replications was used with three groundnut varieties; (ICGV-SM-99568, ICGV SM-01514 and JL-24) as the main plot and three harvesting dates (10 days before physiological maturity, at physiological maturity and 10 days after physiological maturity) and two drying methods; (A-frame and tarpaulin) as the sub-plots. Groundnut samples were analyzed for aflatoxin contamination using immuno-chromatographic assay strips by the M-reader. In both locations, field observations indicated that on average aflatoxin contamination levels were lower at physiological maturity (H2) (≤ 10 ppb) compared to harvesting 10 days before (H1) (≤ 15 ppb) and 10 days after physiological maturity (H3) (≥ 20 ppb). It was also observed that the two drying methods were effective in prevention of aflatoxin contamination on groundnut kernels to levels lower than 20 ppb. However, aflatoxin contamination levels were significantly lower (≤12 ppb) as a result of the A-frame than the tarpaulin method. The results of this study therefore, have indicated that proper post-harvest management of groundnuts such as harvesting at physiological maturity and improved drying gave lowest aflatoxin contamination levels lower than the FDA/WHO regulatory levels of 20 ppb.